Eosinophilic Esophagitis Histology Remission Score: Significant Relations to Measures of Disease Activity and Symptoms. Issue 5 (May 2020) - Collins, Margaret H.; Martin, Lisa J.; Wen, Ting; Abonia, Juan Pablo; Putnam, Philip E.; Mukkada, Vincent A.; Rothenberg, Marc E.
ABSTRACT: Objectives: Eosinophilic esophagitis (EoE) is characterized by remissions and relapses. Guidelines defining remission do not exist and therefore remission is inconsistently identified. We sought to define histology remission in EoE. Methods: Esophageal biopsies, obtained at the time the validated pediatric EoE symptoms scores v2.0 (PEESS v2.0) questionnaire was completed (N = 42), were scored using the validated EoE Histology Scoring System. An EoE Histology Remission Score (EoEHRS) was constructed and specified that in all esophageal sites sampled the peak eosinophil count was <15 per high power field (HPF); in addition, neither the total grade (severity of pathology) nor stage (extent of pathology) scores could exceed 3 (possible total maximum score for each was 24). Spearman correlation coefficients were generated for histology/symptom correlations; coefficient range 0.31 to 0.50 was considered moderate. Results: EoE Histology Scoring System composite and individual feature scores from proximal and distal esophageal biopsies correlated moderately with PEESS v2.0 mean scores (0.48–0.36, P < 0.01), and with scores in the dysphagia (0.39–0.30, P  ⩽ 0.01), pain (0.48–0.34, P  ⩽ 0.01), and gastroesophageal reflux disease (0.51–0.32, P  ⩽ 0.01) domains. Biopsies that met full EoEHRS criteria had reduced biomarkers, specifically expression of the mast cell markers CPA3 and tryptase mRNA, and reduced eosinophil peroxidase deposition ( P  < 0.03), compared to those with nonremission scores. Subjects whose biopsies met EoEHRS remission criteria reported reduced symptoms for all domains except nausea and vomiting ( P  ⩽ 0.01). Conclusions: The EoEHRS correlated with reduced biomarkers of disease activity and reduced symptoms, and therefore may be useful to inform clinical care and interstudy comparisons. Abstract : Supplemental Digital Content is available in the text